(untitled) (Journal of the Bangladesh Agricultural University, 2012)
Pathogenicity of a bacterial isolate Aeromonas hydrophila recovered from naturally diseased shing fish was investigated against catfishes (Heteropneustes fossilis and Clarias batrachus), carps (Labeo rohita, Catla catla and Cirrhinus cirrhosus) and perch (Anabas testudineus) of average body weight of 20.4 g for H. fossilis, 25.6 g for C. Batrachus, 35.2 g for L. rohita, 25.7 g for C. catla, 30.5 g for C. cirrhosus and 20.3 g for A. testudineus. Two different doses viz. 6.7 × 106 and 6.7 × 105 CFU/fish were injected intramuscularly. Pathogenicity of A. hydrophila was confirmed at water temperature of 30°C by mortality of 60% to 100% of all the tested fishes within 2-11 days. Injected A. hydrophila was re-isolated from liver, kidney and intestine of all the tested fishes. The highest bacterial loads in catfishes were found to be 5.5 × 108 CFU/g in the liver of H. fossilis and 5.6 × 107 CFU/g in the intestine of C. batrachus. The lowest bacterial loads were found to be 2.2 × 102 CFU/g in the kidney of H. fossilis and 2.4 × 103 CFU/g in the liver of C. batrachus. The highest bacterial loads in carps were found to be 4.9 × 109 CFU/g in the liver of C. catla, 7.7 × 108 CFU/g in the intestine of L. rohita and 5.8 × 108 CFU/g in the intestine of C. cirrhosus. The lowest bacterial loads were found to be 2.7 × 104 CFU/g in the kidney of C. catla, 3.0 ×104 CFU/g in the kidney of L rohita and 5.6 × 103 CFU/g in the kidney of C. cirrhosus. The highest and lowest bacterial load in perch was found to be 6.4 × 10’ CFU/g and 1.6 × 102 CFU/g in the intestine and kidney of A. testudineus respectively. In all the cases of intramuscular injection, external pathology was found. Reddish anal region and fm bases were observed. It was understood that the isolate was a highly virulent pathogen for the challenged fishes. DOI: http://dx.doi.org/10.3329/jbau.v10i1.12108 J. Bangladesh Agril. Univ. 10(1): 157161, 2012